An Evaluation Of Physio-Chemical And Functional Properties Of Vegetables Through Different Drying Methods - Anukriti, Singh Neetu (International Journal of Modern Agriculture, 2021)
The impact of solar and sun drying on physical properties of vegetable samples was determined. Ash content of sun and solar dried samples were significantly (p<0.05) increased compared to fresh samples. Ash content of spinach, Fenugreek, Cauliflower, Tomato, Chenopodium treated under sundry were (16.05± 0.03), (3.23± 0.14),( 6.57± 0.28),( 1.01± 0.01),( 4.31± 0.16) respectively while ash content of spinach, Fenugreek, Cauliflower, Tomato, Chenopodium treated under solar dry were (17.63± 0.31), (3.33± 0.17), (7.80± 0.11), (2.01± 0.05), (5.33± 0.14) respectively. Angle of repose of spinach, Fenugreek, Cauliflower, Tomato, Chenopodium treated under sundry were (40.71±0.31), (30.70±0.30), (99.76±0.39), (65.43±0.43), (49.46±0.51) orderly while Angle of repose of spinach, Fenugreek, Cauliflower, Tomato, Chenopodium treated under solar dry were (41.28±0.30), (44.26±0.36), (105.10), (67.19±0.93), (57.62±1.47) respectively. True density of spinach, Fenugreek, Cauliflower, Tomato, Chenopodium treated under sundry were (783.00±3.00), (749.66±4.63), (285.00±2.30), (347.46±3.05), (147.73±4.77) sequentially while True density of spinach, Fenugreek, Cauliflower, Tomato, Chenopodium treated under solar dry were (901.95±2.53), (850.29±0.35), (296.66±0.88), (358.06±3.47), (147.73±0.81) successively. All methods of drying found to significantly (p<0.05) lower moisture, Ash, angle of repose, bulk density , true density, hydration and water absorption capacity in compare to their fresh samples. In respect to density the bulk density and true density was quit low in sundried vegetable samples relative to solar dried vegetable samples. Swelling index, swelling capacity, hydration level, water solubility were seen reduced in sun dried vegetable samples rather than solar dried. Solar drying may be preferred method of drying the vegetable samples, as it is faster more hygienic preserve the nutrients better.